Î³-Radiation â€œAgingâ€ of Thin Film TiO2 - Slezak, Kevin Clark (Proceedings of the Wisconsin Space Conference, 2017)
Titanium dioxide (TiO2), a wide-bandgap semiconductor, has in recent decades been the subject of intense scientific study due to its photoactive properties.Â Although TiO2 has been thoroughly researched in projects regarding applications of those properties, few, if any, have focused on how the electrical and structural properties change over long term exposure to damaging high energy radiation.Â This type of radiation can alter the atomic structure of the material which leads to changes in characteristic properties.Â Our present study seeks to understand the long and short term effects that exposure to high energy radiation has on TiO2. Â Â We exposed thin films of TiO2 to a 137Cs (661.8 keV) Î³-radiation source for varying amounts of time.Â After irradiation, the structural, optical, and electrical properties were fully characterized to examine the impact of radiation exposure on this technologically important material.Â Â